Method for preparing water-soluble double salt flame-retardant system polyvinyl alcohol composite film material based on glycerophosphate plasticizing modification
Patent Information
- Application Number
- CN202611263886.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-20
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-08-20
AI Technical Summary
但传统刚性阻燃剂的加入在破坏聚合物连续相而削弱力学性能的同时,其致密的交联网络会严重阻碍水分子向PVA基体内部的渗透扩散,导致溶解过程出现明显的迟滞现象,难以满足绿色包装快速水化崩解的生态消纳需求
[0040]1、本发明提供了一种基于磷酸甘油酯增塑改性制备水溶性双盐阻燃体系聚乙烯醇复合膜材的方法,该方法创新性地以磷酸甘油酯替代传统甘油作为增塑剂,并复配木质素磺酸钠(SLS-Na)与氨基磺酸胍(GAS)构建水溶性双盐阻燃体系,多组分的协同作用使得该膜材具有良好的力学增强、阻燃安全与水溶特性。
Smart Images

Figure CN122810417B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of functional polyvinyl alcohol composite film technology, and relates to a method for preparing a water-soluble dual-salt flame-retardant polyvinyl alcohol composite film based on glycerol phosphate plasticizing modification. This polyvinyl alcohol composite film can be used to prepare packaging materials. Background Technology
[0002] With the expansion of the global consumer goods market, the consumption of single-use flexible packaging materials has increased dramatically. Traditional non-degradable plastic packaging tends to remain in soil and water bodies for extended periods after disposal, eventually breaking down into microplastics and causing sustained harm to ecosystems. To alleviate this environmental pressure, developing green packaging films that can rapidly disintegrate and be ecologically harmlessly disposed of using natural aqueous solutions after use has become a key research direction in the field of polymer materials. Practical applications place stringent requirements on the comprehensive performance of such films. On the one hand, the material must possess excellent mechanical load-bearing capacity and flame retardant safety during its dry service life to cope with mechanical damage during logistics transportation and fire hazards during intensive storage. On the other hand, after contact with an aqueous phase upon disposal, the material must break down the physical barriers of the polymer network, achieving rapid disintegration within minutes to avoid long-term physical retention in nature. Therefore, constructing film materials that combine mechanical strength, high flame retardancy, and rapid water solubility is crucial for developing new rapid-disposal green packaging.
[0003] Polyvinyl alcohol (PVA) is widely used in the preparation of environmentally friendly packaging films due to its tunable water solubility, excellent film-forming properties, and biocompatibility. Compared with solution casting, thermoplastic extrusion processing of PVA is more suitable for large-scale continuous industrial production. However, due to the dense hydrogen bond network between PVA molecular chains, industrial processing usually requires the introduction of polyols such as glycerol for plasticization to improve its flowability. Glycerol, as a highly hydrophilic and flammable small molecule, is not only prone to migration during service, leading to the degradation of the film's mechanical properties, but also significantly increases the heat release rate of the system, making packaging materials for dense storage face a higher fire risk (Fei W, Wu Z, Cheng H, et al. Molecular mobility and morphologychange of poly (vinyl alcohol)(PVA) film as induced by plasticizer glycerol[J]. Journal of Polymer Science, 2023, 61(17): 1959-1970.).
[0004] To improve the flame retardant properties of PVA, existing studies have introduced rigid phosphorus-containing (Wang X, Li Y, Meng D, et al. A review on flame-retardant polyvinyl alcohol: additives and technologies[J]. Polymer Reviews, 2023, 63(2): 324-364.), nitrogen-containing (Yu Z, Liu J, He H, et al. Flame-retardant PNIPAAm / sodium alginate / polyvinyl alcohol hydrogels used for fire-fighting application: Preparation and characteristic evaluations[J]. Carbohydrate Polymers, 2021, 255: 117485.), or intumescent flame retardant systems (Xuan Z, Xu W, Qin Z, et al. Green and Thermostable Bio-Based Flame Retardant System: A New Strategy for Preparing Flame-Retardant Polyvinyl Alcohol Materials via Melt Processing[J]. Polymer Degradation and Stability, 2026: 111953.). However, the addition of traditional rigid flame retardants not only disrupts the continuous phase of the polymer and weakens its mechanical properties, but its dense cross-linked network also severely hinders the penetration and diffusion of water molecules into the PVA matrix, resulting in a significant lag in the dissolution process, making it difficult to meet the ecological disposal requirements of rapid hydration and disintegration in green packaging.
[0005] Therefore, it is necessary to provide a polyvinyl alcohol composite film technology solution that combines thermoplastic processability, reinforcing effect, flame retardant safety, and water solubility. Summary of the Invention
[0006] This invention addresses the shortcomings of existing technologies by providing a method for preparing a water-soluble dual-salt flame-retardant polyvinyl alcohol composite film based on glyceryl phosphate plasticizer modification. This method innovatively uses glyceryl phosphate instead of traditional glycerol as a plasticizer and combines it with sodium lignosulfonate (SLS-Na) and guanidine aminosulfonate (GAS) to construct a water-soluble dual-salt flame-retardant system. The synergistic effect of these multiple components gives the film excellent mechanical reinforcement, flame-retardant safety, and water solubility. This invention not only provides a high-performance, environmentally friendly alternative material for solving logistics packaging problems but also provides a theoretical basis for balancing the multifunctionality of polymer films.
[0007] To achieve the above objectives, the present invention employs a technical solution consisting of the following technical measures.
[0008] This invention provides a method for preparing a water-soluble dual-salt flame-retardant polyvinyl alcohol composite film based on glycerol phosphate plasticizing modification, comprising the following steps:
[0009] (1) By mass parts, the following raw material components are mixed and then subjected to swelling and plasticizing modification to obtain pre-plasticized PVA:
[0010] 50-70 servings of PVA
[0011] 5-15 parts of glyceryl phosphate
[0012] 20-35 parts deionized water
[0013] 5-15 parts of water-soluble flame retardant;
[0014] The water-soluble flame retardant is sodium lignosulfonate and guanidine aminosulfonate;
[0015] (2) The preplasticized PVA obtained in step (1) is melt-extruded and granulated to prepare PVA composite granules;
[0016] (3) The PVA composite granules obtained in step (2) are hot-pressed into a film and then dried to prepare a water-soluble double salt flame retardant polyvinyl alcohol composite film.
[0017] The first inventive point of this invention is that it innovatively uses glyceryl phosphate instead of traditional glycerol as a plasticizer for polyvinyl alcohol (PVA).
[0018] It should be noted that there are numerous existing reports on the use of glyceryl phosphate as a plasticizer in PVC plastics. Furthermore, when glyceryl phosphate is used as a plasticizer in PVC plastics, it does not antagonize other plasticizers and therefore does not significantly negatively impact the processing performance of PVC. However, the inventors, through extensive research, found no reports on the application of glyceryl phosphate in the thermoplastic processing system of PVA.
[0019] For the thermoplastic processing of PVA, traditional systems often use water and polyols as composite plasticizers. However, since polyols themselves are flammable, they significantly reduce the flame retardant properties of PVA products. Therefore, when using polyols as plasticizer components, especially glycerin, improving their flame retardancy requires the addition of a large amount of flame retardant. This inevitably leads to a deterioration in the mechanical properties of the plasticized and modified PVA thermoplastic products, while also increasing costs.
[0020] If water is chosen as the plasticizer for PVA, the prepared PVA film is prone to continuous volatilization during application and is difficult to maintain in the form of bound water in PVA for a long time. This leads to the PVA film drying and hardening, a decrease in elongation at break, and a decrease in water solubility. Therefore, water cannot be used as the plasticizer alone.
[0021] Therefore, the inventors noticed that glyceryl phosphate, while possessing flame-retardant functional groups, could also be used as a plasticizer. However, due to the need to balance water solubility and flame retardancy, only a composite plasticizer of water and glyceryl phosphate could be used. In preliminary exploratory experiments, it was discovered that glyceryl phosphate competitively binds with PVA and water, causing water molecules that were originally well-bonded with the PVA network to be released and converted into free water. In the high-temperature environment of traditional continuous thermoplastic processing, such as melt extrusion casting or blown film forming processes, this free water is easily vaporized by heat, thus forming dense microporous defects inside the film material (e.g., Figure 1 As shown in the figure, this makes it impossible to prepare a dense PVA film. This also explains why there are no reports on the application of glycerol phosphate in the thermoplastic processing system of PVA.
[0022] To address the aforementioned issues, this invention employs a processing technique involving plasticization modification, melt extrusion granulation, and subsequent hot pressing to form a film. This process, completed in a high-temperature, closed system, maintains pressure until the system cools to room temperature, effectively suppressing the vaporization of free water during high-temperature processing. This method overcomes microporous defects caused by moisture loss, achieving homogeneous coexistence and good compatibility of the water, glycerol phosphate, and PVA ternary system, ultimately producing a dense, transparent polyvinyl alcohol film with excellent mechanical properties (such as...). Figure 2 (As shown).
[0023] However, during the above process, it was found that glycerol phosphate forms multi-point hydrogen bonds with PVA, and may also induce localized chain segment ordering through phosphorus-containing groups. This means that water molecules need to break strong inter-chain interactions before they can disentangle and diffuse. Therefore, while simply replacing glycerol with glycerol phosphate can improve mechanical strength, it also leads to a decrease in water solubility.
[0024] The second inventive aspect of this invention lies in the introduction of sodium lignosulfonate and guanidine aminosulfonate as water-soluble flame retardants to construct a dual-salt flame-retardant system. The introduction of sodium lignosulfonate and guanidine aminosulfonate alters the mass transfer path of water after it enters the film: due to their excellent water solubility, they preferentially dissolve upon contact with water, effectively introducing a "sacrificial" water-soluble template into the PVA matrix; the micropores and channels left by the template's dissolution shorten the diffusion path of water molecules, transforming the dissolution process from surface-to-layer erosion to simultaneous surface swelling and internal penetration. Based on this system, the prepared polyvinyl alcohol composite film exhibits excellent water solubility and flame retardancy.
[0025] In this article, the PVA mentioned in step (1) is called polyvinyl alcohol in Chinese. It is a conventional chemical raw material, usually in granules.
[0026] In one of the technical solutions, the PVA mentioned in step (1) is preferably a polyvinyl alcohol with a degree of polymerization of 1500~2400 and a degree of hydrolysis of 88~92%; more preferably a polyvinyl alcohol with a degree of polymerization of 1700 and a degree of hydrolysis of 88%.
[0027] In this paper, the following raw material components are mixed in step (1) and then subjected to swelling and plasticizing modification to obtain pre-plasticized PVA. The technical principle of swelling and plasticizing modification is mainly based on the research results in the prior art (Wang Ru, Wang Qi, Li Li, et al. Thermal properties of modified polyvinyl alcohol [J]. Plastics Industry, 2002, 30(1):3.). Therefore, those skilled in the art can directly refer to the above literature or conventional process methods in the prior art to know the specific swelling and plasticizing modification process method.
[0028] To better illustrate the present invention and provide a technical solution for reference, the swelling and plasticizing modification described in step (1) involves first mixing glyceryl phosphate, deionized water and water-soluble flame retardant evenly to prepare a plasticizing flame retardant solution, and then fully mixing the plasticizing flame retardant solution with PVA so that the plasticizing flame retardant solution evenly coats the surface of PVA, and then sealing and keeping it at a temperature of 50~70 ℃ for 24~72 h.
[0029] In one preferred embodiment, based on the results of a variable comparison test, in order to improve the flame retardancy and water solubility of the prepared polyvinyl alcohol composite film, the water-soluble flame retardant is sodium lignosulfonate and guanidine aminosulfonate, and the mass ratio of sodium lignosulfonate to guanidine aminosulfonate is (1~4):(1~4).
[0030] Furthermore, to further improve the flame retardancy of the prepared polyvinyl alcohol composite film, the preferred mass ratio of sodium lignosulfonate to guanidine aminosulfonate is (2~3):(7~8).
[0031] To further improve the water solubility of the prepared polyvinyl alcohol composite film, the mass ratio of sodium lignosulfonate to guanidine aminosulfonate is (7~8):(2~3).
[0032] In one technical solution, during the melt extrusion granulation process in step (2), conventionally used additives in PVA processing and molding can be added to further extend the product's functionality / process aids. For specific additive selection, those skilled in the art can refer to existing technologies or literature, such as defoamers, antioxidants, heat stabilizers, antibacterial agents, and other processing aids / functional additives. It should be noted that during the melt extrusion granulation process in step (2), conventionally used additives in PVA processing and molding can be added, or not. In the preferred technical solutions and specific embodiments described below, to minimize the influence factors in the comparative experiments, additives were not added during the melt extrusion granulation process, but this does not mean that appropriate additives cannot be added. Generally, the total mass of added additives should not exceed 10 wt% of the mass of the preplasticized PVA.
[0033] In this article, the preplasticized PVA described in step (2) is melt-extruded and granulated to prepare PVA composite granules, which is a conventional screw extrusion granulation process. Those skilled in the art can directly refer to the extrusion granulation process of PVA, such as the previously published invention patent application "Method adapted to blow molding to prepare high performance PVA / PBAT composite film" (CN120040810A).
[0034] In one preferred embodiment, the preplasticized PVA in step (2) is melt-extruded and granulated using a screw extruder with the temperature of each zone set to 80~135 ℃ and the screw speed set to 15~35 rpm.
[0035] In one of the preferred technical solutions, the PVA composite granules described in step (3) are hot-pressed into a film by spreading the PVA composite granules flat in a hot-pressing mold, hot-pressing them into a film at 160~190 ℃ and 5~10 MPa, and then cooling them to room temperature (23~27 ℃) under pressure.
[0036] In one preferred embodiment, the drying process in step (3) is performed at a temperature of 40-90 °C for 12-48 h.
[0037] In this document, the mixing process follows conventional principles in chemical processes, and those skilled in the art can perform specific operations based on common knowledge.
[0038] The water-soluble dual-salt flame-retardant polyvinyl alcohol composite membrane material prepared by this invention can be used for logistics packaging, centralized warehousing packaging, water treatment and recycling packaging, soluble protective films, and disposable green packaging materials. In service, this composite membrane material provides good mechanical integrity and flame-retardant safety; in recycling or water treatment environments, the water-soluble flame retardant preferentially dissolves and forms pores, which is beneficial for further hydration, disintegration, and volume reduction of the membrane material.
[0039] The present invention has the following beneficial effects:
[0040] 1. This invention provides a method for preparing a water-soluble dual-salt flame-retardant polyvinyl alcohol composite membrane based on glyceryl phosphate plasticizing modification. This method innovatively uses glyceryl phosphate to replace traditional glycerol as a plasticizer, and combines sodium lignosulfonate (SLS-Na) and guanidine aminosulfonate (GAS) to construct a water-soluble dual-salt flame-retardant system. The synergistic effect of the multiple components gives the membrane good mechanical reinforcement, flame retardant safety and water solubility.
[0041] 2. In this invention, glyceryl phosphate acts as a plasticizer to improve the thermoplastic processability of polyvinyl alcohol (PVA). Furthermore, it can form hydrogen bonds with PVA segments through hydroxyl and phosphorus-containing groups, enhancing segmental constraint. Sodium lignosulfonate provides an aromatic / lignin-based charcoal framework, while guanidine aminosulfonate provides both acid and gas sources. When combined, these components form dispersed nodes or microcrystalline nodes in the dry membrane material. During combustion, they participate in the synergistic flame retardancy of the acid-gas-char source, and in an aqueous environment, they preferentially dissolve and form channels, thereby promoting membrane hydration and disintegration.
[0042] 3. In one technical solution, by adjusting the compounding ratio of sodium lignosulfonate and guanidine aminosulfonate, a specific microstructure of "hydrogen bond association and salt phase dispersion" is constructed inside the composite membrane material. This structure enables the composite membrane material to not only maintain high load-bearing capacity in the dry state and form an effective char layer shield during combustion, but also to generate micropores in situ through preferential dissolution of the salt phase after contact with water, thereby accelerating dissolution.
[0043] 4. The method of this invention is simple and can be directly applied to existing polyvinyl alcohol film preparation systems. This invention proposes and verifies the design concept of synergistically balancing multiple properties of polymer films by regulating hydrogen bond networks and salt phase pore formation, providing a solid theoretical basis for developing new green packaging materials that meet the requirements of industrial processing, dense storage safety and rapid ecological disposal. Attached Figure Description
[0044] Figure 1 This is a photograph of the PVA film prepared in Comparative Example 4 of this invention.
[0045] Figure 2 This is a photograph of the "dry thin film" sample prepared in Comparative Example 2 of this invention.
[0046] Figure 3 The images show the FTIR curves of the "dry thin film" samples prepared in Examples 1-3 and Comparative Examples 1-4 of this invention.
[0047] Figure 4 The XRD curves (a) and the bar charts (b) comparing the crystallinity of the PVA phase are shown for the "dry thin film" samples prepared in Examples 1-3 and Comparative Examples 1-4 of this invention.
[0048] Figure 5 Figure 1 shows a summary of the mechanical properties of the samples prepared in Examples 1-3 and Comparative Examples 1-4 of this invention. Specifically, Figure (a) is a comparison of the tensile stress-strain curves of the "wet film" samples prepared in Examples 1-3 and Comparative Examples 1-4; Figure (b) is a comparison of the tensile stress-strain curves of the "dry film" samples prepared in Examples 1-3 and Comparative Examples 1-4; Figure (c) is a bar chart comparing the tensile strength of the "wet film" and "dry film" samples prepared in Examples 1-3 and Comparative Examples 1-4; and Figure (d) is a bar chart comparing the elongation at break of the "wet film" and "dry film" samples prepared in Examples 1-3 and Comparative Examples 1-4.
[0049] Figure 6 This is a comparative bar chart showing the limiting oxygen index of the "dry thin film" samples prepared in Examples 1-3 and Comparative Examples 2-4 of the present invention.
[0050] Figure 7 The figures (a) and (b) show a comparison of the mass loss rate curves of the "dry thin film" samples prepared in Examples 1-3 and Comparative Examples 1-4 of this invention at different dissolution times.
[0051] Figure 8 Scanning electron microscope (SEM) images of the cross-sections of the "dry thin film" samples prepared in Comparative Examples 1 and 2 of this invention. Figure (a) is an SEM image of the cross-section of the "dry thin film" sample prepared in Comparative Example 1; Figure (b) is an SEM image of the cross-section of the "dry thin film" sample prepared in Comparative Example 2.
[0052] Figure 9 These are scanning electron microscope (SEM) images of the cross-sections of the "dry thin film" samples prepared in Examples 2 and 3-4 of this invention. Figures (a) to (c) are SEM images of the cross-sections of the "dry thin film" samples prepared in Comparative Examples 3, 4, and 2, respectively; Figures (d) to (f) are magnified views of specific sections. Detailed Implementation
[0053] To further understand the present invention, preferred embodiments are described below with reference to examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, and not for limiting the scope of the claims. Those skilled in the art can refer to the content of this document to appropriately improve the process parameters. In particular, it should be noted that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included within the scope of the present invention. The methods and applications of the present invention have been described through preferred embodiments, and those skilled in the art can obviously make modifications or appropriate changes and combinations to the methods and applications described herein without departing from the content, spirit and scope of the present invention to realize and apply the technology of the present invention. Although it is believed that those skilled in the art will fully understand the following terms, the following definitions are set forth to help illustrate the subject matter disclosed in the present invention.
[0054] This invention provides a method for preparing a water-soluble dual-salt flame-retardant polyvinyl alcohol composite film based on glycerol phosphate plasticizing modification, comprising the following steps:
[0055] (1) By mass parts, the following raw material components are mixed and then subjected to swelling and plasticizing modification to obtain pre-plasticized PVA:
[0056] 50-70 servings of PVA
[0057] 5-15 parts of glyceryl phosphate
[0058] 20-35 parts deionized water
[0059] 5-15 parts of water-soluble flame retardant;
[0060] The water-soluble flame retardant is sodium lignosulfonate and guanidine aminosulfonate;
[0061] (2) The preplasticized PVA obtained in step (1) is melt-extruded and granulated to prepare PVA composite granules;
[0062] (3) The PVA composite granules obtained in step (2) are hot-pressed into a film and then dried to prepare a water-soluble double salt flame retardant polyvinyl alcohol composite film.
[0063] The first inventive point of this invention is that it innovatively uses glyceryl phosphate instead of traditional glycerol as a plasticizer for polyvinyl alcohol (PVA).
[0064] It should be noted that there are numerous existing reports on the use of glyceryl phosphate as a plasticizer in PVC plastics. Furthermore, when glyceryl phosphate is used as a plasticizer in PVC plastics, it does not antagonize other plasticizers and therefore does not significantly negatively impact the processing performance of PVC. However, the inventors, through extensive research, found no reports on the application of glyceryl phosphate in the thermoplastic processing system of PVA.
[0065] For the thermoplastic processing of PVA, traditional systems often use water and polyols as composite plasticizers. However, since polyols themselves are flammable, they significantly reduce the flame retardant properties of PVA products. Therefore, when using polyols as plasticizer components, especially glycerin, improving their flame retardancy requires the addition of a large amount of flame retardant. This inevitably leads to a deterioration in the mechanical properties of the plasticized and modified PVA thermoplastic products, while also increasing costs.
[0066] If water is chosen as the plasticizer for PVA, the prepared PVA film is prone to continuous volatilization during application and is difficult to maintain in the form of bound water in PVA for a long time. This leads to the PVA film drying and hardening, a decrease in elongation at break, and a decrease in water solubility. Therefore, water cannot be used as the plasticizer alone.
[0067] Therefore, the inventors noticed that glyceryl phosphate, while possessing flame-retardant functional groups, could also be used as a plasticizer. However, due to the need to balance water solubility and flame retardancy, only a composite plasticizer of water and glyceryl phosphate could be used. In preliminary exploratory experiments, it was discovered that glyceryl phosphate competitively binds with PVA and water, causing water molecules that were originally well-bonded with the PVA network to be released and converted into free water. In the high-temperature environment of traditional continuous thermoplastic processing, such as melt extrusion casting or blown film forming processes, this free water is easily vaporized by heat, thus forming dense microporous defects inside the film material (e.g., Figure 1 As shown in the figure, this makes it impossible to prepare a dense PVA film. This also explains why there are no reports on the application of glycerol phosphate in the thermoplastic processing system of PVA.
[0068] To address the aforementioned issues, this invention employs a processing technique involving plasticization modification, melt extrusion granulation, and subsequent hot pressing to form a film. This process, completed in a high-temperature, closed system, maintains pressure until the system cools to room temperature, effectively suppressing the vaporization of free water during high-temperature processing. This method overcomes microporous defects caused by moisture loss, achieving homogeneous coexistence and good compatibility of the water, glycerol phosphate, and PVA ternary system, ultimately producing a dense, transparent polyvinyl alcohol film with excellent mechanical properties (such as...). Figure 2 (As shown).
[0069] However, during the above process, it was found that glycerol phosphate forms multi-point hydrogen bonds with PVA, and may also induce localized chain segment ordering through phosphorus-containing groups. This means that water molecules need to break strong inter-chain interactions before they can disentangle and diffuse. Therefore, while simply replacing glycerol with glycerol phosphate can improve mechanical strength, it also leads to a decrease in water solubility.
[0070] The second inventive aspect of this invention lies in the introduction of sodium lignosulfonate and guanidine aminosulfonate as water-soluble flame retardants to construct a dual-salt flame-retardant system. The introduction of sodium lignosulfonate and guanidine aminosulfonate alters the mass transfer path of water after it enters the film: due to their excellent water solubility, they preferentially dissolve upon contact with water, effectively introducing a "sacrificial" water-soluble template into the PVA matrix; the micropores and channels left by the template's dissolution shorten the diffusion path of water molecules, transforming the dissolution process from surface-to-layer erosion to simultaneous surface swelling and internal penetration. Based on this system, the prepared polyvinyl alcohol composite film exhibits excellent water solubility and flame retardancy.
[0071] In this article, the PVA mentioned in step (1) is called polyvinyl alcohol in Chinese. It is a conventional chemical raw material, usually in granules.
[0072] In one embodiment, the PVA mentioned in step (1) is preferably a polyvinyl alcohol with a degree of polymerization of 1500 to 2400 and a degree of hydrolysis of 88 to 92%; more preferably a polyvinyl alcohol with a degree of polymerization of 1700 and a degree of hydrolysis of 88%.
[0073] In this paper, the following raw material components are mixed in step (1) and then subjected to swelling and plasticizing modification to obtain pre-plasticized PVA. The technical principle of swelling and plasticizing modification is mainly based on the research results in the prior art (Wang Ru, Wang Qi, Li Li, et al. Thermal properties of modified polyvinyl alcohol [J]. Plastics Industry, 2002, 30(1):3.). Therefore, those skilled in the art can directly refer to the above literature or conventional process methods in the prior art to know the specific swelling and plasticizing modification process method.
[0074] To better illustrate the present invention and provide an embodiment for reference, the swelling and plasticizing modification described in step (1) involves first mixing glyceryl phosphate, deionized water and water-soluble flame retardant evenly to prepare a plasticizing flame retardant solution, and then fully mixing the plasticizing flame retardant solution with PVA so that the plasticizing flame retardant solution evenly coats the surface of PVA, and then sealing and keeping it at a temperature of 50~70 ℃ for 24~72 h.
[0075] In one preferred embodiment, based on the results of a variable comparison test, in order to improve the flame retardancy and water solubility of the prepared polyvinyl alcohol composite film, the water-soluble flame retardant is sodium lignosulfonate and guanidine aminosulfonate, and the mass ratio of sodium lignosulfonate to guanidine aminosulfonate is (1~4):(1~4).
[0076] Furthermore, to further improve the flame retardancy of the prepared polyvinyl alcohol composite film, the preferred mass ratio of sodium lignosulfonate to guanidine aminosulfonate is (2~3):(7~8).
[0077] To further improve the water solubility of the prepared polyvinyl alcohol composite film, the mass ratio of sodium lignosulfonate to guanidine aminosulfonate is (7~8):(2~3).
[0078] In one embodiment, the PVA in step (1) is 50 to 70 parts, for example, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70 parts, or any range or point value between them; the glyceryl phosphate is 5 to 15 parts, for example, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 parts. The deionized water is 20-35 parts, for example, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35 parts, or any range or value between them; the water-soluble flame retardant is 5-15 parts, for example, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 parts, or any range or value between them.
[0079] In one embodiment, during the melt extrusion granulation process in step (2), conventionally used additives in PVA processing and molding may be added to further extend the product's functionality / process aids. For specific additive selection, those skilled in the art can refer to existing technologies or literature, such as defoamers, antioxidants, heat stabilizers, antibacterial agents, and other processing aids / functional additives. Note that during the melt extrusion granulation process in step (2), conventionally used additives in PVA processing and molding may or may not be added. In the preferred technical solutions and specific embodiments described below, to minimize the influence factors in the comparative experiments, additives were not added during the melt extrusion granulation process, but this does not mean that appropriate additives cannot be added. Generally, the total mass of added additives should not exceed 10 wt% of the preplasticized PVA mass.
[0080] In this article, the preplasticized PVA described in step (2) is melt-extruded and granulated to prepare PVA composite granules, which is a conventional screw extrusion granulation process. Those skilled in the art can directly refer to the extrusion granulation process of PVA, such as the previously published invention patent application "Method adapted to blow molding to prepare high performance PVA / PBAT composite film" (CN120040810A).
[0081] In one preferred embodiment, the preplasticized PVA in step (2) is melt-extruded and granulated using a screw extruder with the temperature of each zone set to 80~135 ℃ and the screw speed set to 15~35 rpm.
[0082] In one preferred embodiment, the PVA composite granules described in step (3) are hot-pressed into a film by spreading the PVA composite granules flat in a hot-pressing mold and hot-pressing them into a film at 160~190 ℃ and 5~10 MPa, and then cooling them to room temperature (23~27 ℃) under pressure.
[0083] In one preferred embodiment, the drying process in step (3) is performed at a temperature of 40~90 °C for 12~48 h.
[0084] In this document, the mixing process follows conventional principles in chemical processes, and those skilled in the art can perform specific operations based on common knowledge.
[0085] The water-soluble dual-salt flame-retardant polyvinyl alcohol composite membrane material prepared by this invention can be used for logistics packaging, centralized warehousing packaging, water treatment and recycling packaging, soluble protective films, and disposable green packaging materials. In service, this composite membrane material provides good mechanical integrity and flame-retardant safety; in recycling or water treatment environments, the water-soluble flame retardant preferentially dissolves and forms pores, which is beneficial for further hydration, disintegration, and volume reduction of the membrane material.
[0086] The present application will be further explained in detail below with reference to embodiments. However, those skilled in the art should understand that these embodiments are provided for illustrative purposes only and are not intended to limit the present application.
[0087] Example
[0088] The embodiments of this application will be described in detail below with reference to examples. However, those skilled in the art will understand that the following examples are for illustrative purposes only and should not be construed as limiting the scope of this application. Where specific conditions are not specified in the examples, conventional conditions or conditions recommended by the manufacturer shall apply. Where the manufacturers of reagents or instruments are not specified, they are all commercially available conventional products. This application should not be construed as being limited to the specific embodiments described.
[0089] 1. Raw materials
[0090] Polyvinyl alcohol (PVA1788, degree of alcoholysis 88%, degree of polymerization 1700) was purchased from Chongqing Chuanwei Chemical Co., Ltd., a subsidiary of China Petrochemical Corporation.
[0091] Glycerol (analytical grade), glyceryl phosphate (analytical grade), sodium lignosulfonate (SLS-Na, industrial grade) and guanidine aminosulfonate (GAS, analytical grade) were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0092] Deionized (DI) water is prepared by an ultrapure water system from Sichuan Youpu Ultrapure Technology Co., Ltd.
[0093] All reagents were not further purified before use.
[0094] 2. Preparation method
[0095] (1) By mass parts, the following raw material components are mixed and then subjected to swelling and plasticizing modification to obtain pre-plasticized PVA:
[0096] PVA1788, 50-70 servings.
[0097] 5-15 parts of glyceryl phosphate
[0098] 20-35 parts deionized water
[0099] 5-15 parts of water-soluble flame retardant;
[0100] The water-soluble flame retardant is sodium lignosulfonate and guanidine aminosulfonate;
[0101] The swelling and plasticizing modification involves first mixing glyceryl phosphate, deionized water, and water-soluble flame retardant evenly to prepare a plasticizing and flame-retardant solution. Then, the plasticizing and flame-retardant solution is thoroughly mixed with PVA1788 granules to ensure that the plasticizing and flame-retardant solution uniformly coats the surface of the PVA1788 granules. The mixture is then sealed and kept warm at 60 ℃ for 48 h.
[0102] (2) The preplasticized PVA obtained in step (1) is melt-extruded and granulated to prepare PVA composite granules;
[0103] The melt extrusion granulation is carried out using a screw extruder with the temperature of each zone set to 80~135 ℃ and the screw speed set to 25 rpm.
[0104] (3) The PVA composite granules obtained in step (2) are spread in a hot press mold, and hot-pressed into a film at 175 ℃ and 10 MPa. The film is then cooled to 25 ℃ under pressure. The wet original film obtained after demolding is defined as "wet film".
[0105] The water-soluble double-salt flame-retardant polyvinyl alcohol composite film was then dried at 40 ℃ for 24 h to prepare a "dry film".
[0106] 3. Testing Methods
[0107] Fourier transform infrared spectroscopy (FTIR) was performed in attenuated total reflectance (ATR) mode to test dry thin films, with a scanning range of 4000–400 cm⁻¹. -1 The study used X-ray diffraction (XRD) to analyze the interactions between glycerol phosphate, SLS-Na, GAS, and PVA. XRD was performed on a 200 μm thick film sample using a Rigaku Ultima IV laser from Japan. The radiation source was Cu Kα, the accelerating voltage was 40 kV, the current was 40 mA, the scanning range was 2θ = 5–85°, and the step size was 0.02°. Peak separation and crystallinity calculation were performed using MDI Jade 6 software. Mechanical testing was conducted on both wet and dry film samples. Samples were cut according to GB / T 1040.3 at 25°C and 50% relative humidity (RH) and stretched at a rate of 100 mm / min. Flame retardant properties were evaluated using the "dry film" as the test sample. The limiting oxygen index (LOI) test was performed according to the national standard GB / T2406.2, using a JF-3 oxygen index tester. The vertical burning (UL-94) test was performed according to the national standard GB / T2408-2021, using an LZB-3WB vertical burning tester to assess the sample's rating. In the water solubility test, a film sample with a thickness of approximately 80 μm was cut into 2 cm × 2 cm squares, and the initial mass m0 was recorded. The sample was then stirred in 500 mL of deionized water at 300 rpm. Undissolved residual film was collected at 1, 3, 5, and 10 min, dried, and weighed (m). x The weight loss rate is calculated as M = (m0 - m x Calculate by 100% of m0 / m0, and record the complete dissolution time T. ds Scanning electron microscopy (SEM) was used to observe the cross-sectional morphology of the thin film samples. After liquid nitrogen fracture and gold sputtering, the samples were observed at an accelerating voltage of 4 kV, with magnifications of 2000x and 10000x.
[0108] Examples 1-3, Comparative Examples 1-4
[0109] Examples 1-3 and Comparative Examples 1-4 were prepared by referring to the steps in "2. Preparation Method" above and according to the formulations of each raw material component in Table 1 below to obtain "wet film" samples and "dry film" samples.
[0110] Table 1. Raw material composition formulations (mass fraction / wt%) for Examples 1-3 and Comparative Examples 1-4
[0111]
[0112] In Comparative Example 1, no glyceryl phosphate was added, and traditional water and glycerol were used as composite plasticizers. The resulting sample was denoted as PVAG10.
[0113] In Comparative Example 2, no sodium lignosulfonate and guanidine aminosulfonate were added, and the resulting sample was designated as PVAP10.
[0114] In Comparative Example 3, no sodium lignosulfonate was added, and the resulting sample was designated as PVAP10-1.
[0115] In Comparative Example 4, no guanidine aminosulfonate was added, and the resulting sample was designated as PVAP10-2.
[0116] In Example 1, the mass ratio of sodium lignosulfonate and guanidine aminosulfonate was 5:5, and the resulting sample was denoted as PVAP10-3.
[0117] In Example 2, the mass ratio of sodium lignosulfonate and guanidine aminosulfonate was 7.5:2.5, and the resulting sample was designated as PVAP10-4.
[0118] In Example 3, the mass ratio of sodium lignosulfonate and guanidine aminosulfonate was 2.5:7.5, and the resulting sample was designated as PVAP10-5.
[0119] Comparative Example 4
[0120] In Comparative Example 4, a film sample was prepared using the raw material composition formulation of Comparative Example 2, but following the conventional continuous thermoplastic processing method, including the following steps:
[0121] (I) According to the raw material composition formula of Comparative Example 2, first mix glyceryl phosphate and deionized water evenly to prepare a plasticized flame retardant solution. Then mix the plasticized flame retardant solution with PVA to make the plasticized flame retardant solution evenly coat the PVA surface. Seal and keep warm at 60 ℃ for 48 h.
[0122] (II) The preplasticized PVA obtained in step (I) is melt-extruded and granulated to prepare PVA composite granules;
[0123] In the melt extrusion granulation process, the temperature of each zone of the screw extruder is set to 80~135 ℃, and the screw speed is 25 rpm.
[0124] (III) The PVA composite granules obtained in step (II) are melt-extruded and cast into PVA films and cooled to obtain samples;
[0125] In the melt extrusion casting process, the temperatures of each zone of the single-screw extruder are set to 100 ℃, 120 ℃, and 135 ℃, respectively, the die temperature is 135 ℃, and the screw speed is 15 rpm.
[0126] like Figure 1 As shown, when using traditional continuous thermoplastic processing at high temperatures, dense micropore defects form inside the PVA film.
[0127] like Figure 2 As shown, a dense and transparent polyvinyl alcohol film is prepared by using a processing technology of plasticizing modification followed by melt extrusion granulation and then hot pressing to form a film.
[0128] like Figure 3 As shown, the "dry film" sample was tested by FTIR spectroscopy. The glycerol plasticizer PVAG10 and the glycerol phosphate plasticizer PVAP10 showed similar results in the range of 3200~3500 cm⁻¹. -1 The hydroxyl stretching vibration regions showed differences. The hydroxyl absorption peak of PVAG10 was located at a relatively high wavenumber, while that of PVAP10 shifted towards lower wavenumbers, indicating a strong intermolecular hydrogen bond between the hydroxyl groups in the glycerol phosphate ester and the PVA segments. Simultaneously, the introduction of phosphate groups facilitated the formation of tighter segmental entanglements within the PVA matrix. Furthermore, PVAG10 exhibited a larger hydroxyl absorption peak, which can be attributed to the good water retention capacity of glycerol in dry films, allowing the system to retain more bound water under the same drying conditions. PVAP10 showed a peak at 1080 cm⁻¹. -1 The presence of COP-related characteristic absorption signals nearby indicates that glyceryl phosphate was successfully introduced into the PVA matrix and retained after dehydration and drying. Further addition of SLS-Na and GAS allows the phenolic hydroxyl groups in the SLS-Na structure and the amino groups after GAS dissociation to act as hydrogen bond donors or acceptors, interacting with the PVA segments and glyceryl phosphate to form a bond density of 3000–3500 cm⁻¹. -1 Within the specified range, the broad peak of the hydroxyl / amino overlap stretching vibration broadened and shifted. Therefore, the FTIR results indicate that there are hydrogen bonds and other interactions between glycerol phosphate, SLS-Na / GAS, and PVA segments, which reduce the proportion of intramolecular hydrogen bonds in PVA and thus plasticize the PVA phase.
[0129] like Figure 4As shown in (a), typical diffraction characteristics of PVA1788 can be observed in each "dry film" sample near 2θ = 19.66° and 40.66°. The diffraction peak at 19.66° can be attributed to the (101) crystal plane of PVA, while the diffraction peak near 40.66° is related to crystal planes such as (111) and (210). Compared with PVAG10, the crystallinity of the PVA phase in PVAP10 is increased, which is consistent with the results of enhanced hydrogen bonding by glycerol phosphate in FTIR. Phosphate groups may regulate the hydration state and chain arrangement around PVA segments through the Hofmeister effect, making it easier for the segments to form ordered stacking. Therefore, after replacing glycerol with glycerol phosphate, on the one hand, the interaction between PVA chains is enhanced, and on the other hand, the degree of order of the PVA phase is improved.
[0130] The crystallinity of the PVA phase decreased compared to PVAP10 after the addition of SLS-Na and GAS, indicating that the hydrophilic groups in the two types of water-soluble salts can enter or interfere with the inter-chain arrangement of PVA, resulting in plasticization and amorphization of the PVA segments. Small and sharp crystallization peaks appeared in PVAP10-1 and PVAP10-2 at 2θ=31.92° and 9.16°, respectively, which can be attributed to the local crystallization precipitation of SLS-Na and GAS in the PVA matrix. For PVAP10-3, PVAP10-4, and PVAP10-5, the sharp characteristic peaks of the original single salts were significantly weakened or even disappeared, while more small diffraction peaks appeared, indicating that the two salts interfered with each other during the crystallization process, possibly forming finer and more complex co-eutectoid or microcrystalline structures.
[0131] Figure 4 (b) shows the crystallinity of the PVA phase in each "dry film" sample. From the changes in crystallinity, GAS has a more significant effect on reducing the crystallinity of the PVA phase. Due to the smaller size of GAS molecules, they can more easily enter the inter-chain spaces or local crystalline regions of PVA molecules to exert a plasticizing effect. Therefore, PVAP10-2 is more effective than PVAP10-1 in reducing the crystallinity of the PVA phase. In PVAP10-3 to PVAP10-5, the crystallinity of PVA further decreases with increasing GAS proportions. The crystallinity of PVAP10-5 drops to 18.4%, and no obvious sharp diffraction peaks are observed in the XRD pattern, indicating that the two salts exist mainly in an amorphous or extremely finely dispersed state at this ratio. Thus, the XRD results can distinguish between "PVA matrix crystallinity" and "salt microcrystals / coprecipitation nodes": PVAP10 exhibits higher PVA chain segment order, PVAP10-3 may correspond to more complex salt microcrystals, and PVAP10-5 shows stronger plasticizing and amorphous characteristics.
[0132] like Figure 5As shown, in the "wet film" samples, water molecules act as the main plasticizer, weakening the hydrogen bonds between PVA chains and some crystalline regions, thus maintaining high ductility in all samples. PVAG10 exhibits a wet tensile strength of 16.3 MPa and an elongation at break of 538.4%. After replacing glycerol with glyceryl phosphate, the wet tensile strength of PVAP10 increases to 19.9 MPa, and the elongation at break is 519.6%. Combined with FTIR results, it can be seen that glyceryl phosphate forms strong hydrogen bonds with PVA segments, thus improving the network load-bearing capacity while maintaining wet flexibility. Further introduction of SLS-Na and GAS increases the wet composite film strength to 21.6–39.8 MPa. PVAP10-1 exhibits a high tensile strength of 39.8 MPa in the wet state, but its elongation at break decreases to 361.5%. This result indicates that SLS-Na tends to enhance network constraint in the wet system rather than simply playing a plasticizing role. SLS-Na has a three-dimensional spatial network structure with aromatic structures and sulfonate groups. Its organic hydrophilic part can easily form steric hindrance and local rigid domains between PVA chains, which restricts excessive chain slip. As a small molecule, GAS has hydrophilic groups that can more easily enter the amorphous region or the crystalline / amorphous transition region of PVA, thereby achieving plasticization and chain relaxation of wet PVA films.
[0133] Furthermore, in the "dry film" samples, most of the free water within the film was removed, and the plasticizing mechanism shifted from being dominated by free water to being dominated by the interaction between glycerol phosphate and water-soluble organic salts. Water removal reduced the intersegmental spacing of PVA, enhancing hydrogen bonding and physical cross-linking, thus increasing the strength and decreasing the elongation at break of all samples. The dry tensile strength of PVAP10 was 74.9 MPa, higher than that of PVAG10 (36.3 MPa), indicating that glycerol phosphate not only provides plasticization but also forms effective inter-chain connections with PVA through phosphate groups and hydroxyl groups. XRD analysis revealed that the increased crystallinity of the PVA phase in PVAP10 also contributes to enhanced dry load-bearing capacity; however, this stronger hydrogen bonding and higher orderliness reduces the free movement of chain segments, resulting in a lower dry elongation at break for PVAP10 compared to PVAG10. In the salt composite system, the dry mechanical properties showed a certain correlation with the SLS-Na / GAS ratio. The dry tensile strengths of PVAP10-1 and PVAP10-2 were 80.3 MPa and 97.7 MPa, respectively. After blending, the dry tensile strength of PVAP10-3 reached 130.1 MPa; PVAP10-4 and PVAP10-5 reached 109.0 MPa and 124.7 MPa, respectively. This phenomenon can be attributed to the co-precipitation or formation of fine salt microregions by SLS-Na and GAS, which were originally dissolved in the aqueous phase, during the drying process. These microregions can act as physical nodes to restrict the slippage of PVA chain segments and improve the interfacial load transfer efficiency. When the content of a single salt is too high or the blending ratio deviates, salt crystals may grow or agglomerate, leading to local stress concentration, thus the strength improvement is not as good as that of a balanced blending system.
[0134] like Figure 6As shown, the LOI of PVAP10 sample plasticized with glyceryl phosphate was 19.2%, indicating that a single phosphorus-containing plasticizing system can only provide a limited flame retardant contribution. After adding SLS-Na alone, the LOI of PVAP10-1 increased to 21.3%; after adding GAS alone, the LOI of PVAP10-2 increased to 23.5%. This indicates that both SLS-Na and GAS can improve the combustion inhibition ability of PVA films, but their mechanisms of action differ: SLS-Na is more conducive to solid-phase char formation, while GAS is more conducive to the release of acidic substances and non-flammable gases. The SLS-Na / GAS combination exhibits a synergistic flame retardant effect. The LOIs of PVAP10-3, PVAP10-4, and PVAP10-5 reached 27.5%, 25.2%, and 28.9%, respectively. The reason lies in the fact that SLS-Na provides an aromatic / lignin-based charcoal framework, while the gas and acid sources released by the thermal decomposition of GAS promote the expansion of the char layer. Together, they construct an expanding char layer that provides insulation, oxygen barrier, and inhibits dripping. Among them, PVAP10-2 has a shortened initial extinguishing time during combustion, but due to the lack of a stable charcoal framework, dripping still occurs and ignites the degreased cotton, resulting in a vertical combustion rating of UL94-V2. PVAP10-4, relying on a higher proportion of SLS-Na, constructs a more stable char layer structure, achieving UL94-V0. PVAP10-5, with the combined effect of a higher GAS content and an SLS-Na charcoal framework, achieves a synergistic gas-phase and solid-phase flame retardant mechanism, reaching an LOI of 28.9% and achieving a UL94-V0 rating.
[0135] like Figure 7 As shown, dissolution curves for each "dry film" sample were obtained by collecting residual film mass at fixed times. The complete dissolution time for PVAG10 was 12.2 min, while for PVAP10 it extended to 14.9 min, indicating that the hydrogen bonding / physical crosslinking enhanced by glycerol phosphate and the potentially increased segmental ordering reduce the initial hydration and segmental untangling rates of PVA. After introducing SLS-Na and GAS, the complete dissolution time of the composite film was shortened to 7.1–9.8 min, indicating that the introduction of water-soluble salts effectively offsets the dissolution lag caused by phosphorus-containing crosslinking. The composite film exhibited a two-stage dissolution characteristic of "rapid weight loss followed by gradual deceleration." Initially, surface and shallow salts preferentially dissolve, forming channels within the film and increasing the water / polymer interface area, thereby accelerating PVA hydration and disintegration. Later, as salts and PVA continue to enter the aqueous phase, the increased local ion concentration may produce a certain salting-out effect, slowing down the dissolution rate. The complete dissolution time of PVAP10-1 in the single SLS-Na system was 7.1 min. In the compound system, PVAP10-4 with a higher proportion of SLS-Na also showed faster dissolution, indicating that the greater steric hindrance of SLS-Na makes it easier to disrupt the regular arrangement of PVA and promote water permeation.
[0136] Specifically, comparing PVAP10 and PVAG10 films, glyceryl phosphate forms multi-point hydrogen bonds with PVA and may induce localized chain segment ordering through phosphorus-containing groups. This means that water molecules need to disrupt strong inter-chain interactions before disentanglement and diffusion can occur. Therefore, simply replacing glycerol with glyceryl phosphate increases strength but decreases the water solubility rate. The introduction of SLS-Na and GAS alters the mass transfer path of water after entering the film. Due to their good water solubility, they preferentially dissolve upon contact with water, essentially introducing a "sacrificial" water-soluble template into the PVA matrix. The micropores and channels left by the template shorten the water molecule diffusion path, transforming dissolution from surface-to-layer erosion to simultaneous surface swelling and internal penetration. Different salts promote water solubility to varying degrees. Water solubility tests show that the single SLS-Na system PVAP10-1 dissolves faster than the single GAS system PVAP10-2. This may be related to their molecular size, crystallization state, and local ion concentration after dissolution. SLS-Na molecules are larger and have stronger steric hindrance, making them more likely to disrupt the regular stacking of PVA segments and increase the proportion of amorphous regions. Simultaneously, at the same mass fraction, the molar concentration of free ions generated after dissolution is relatively low, resulting in a weaker inhibitory effect on later salting-out. GAS molecules are smaller and can penetrate deeper into the PVA network and reduce the crystallinity of the PVA phase, but dissolution may also lead to higher local ion concentrations, thus its promoting effect on later complete dissolution is not as good as SLS-Na. Although PVAP10-5 shows the lowest PVA phase crystallinity under XRD, its complete dissolution time is not the shortest, indicating that the water dissolution rate is not solely determined by PVA crystallinity but is also influenced by salt dissolution rate, pore connectivity, and later ion concentration.
[0137] like Figure 8 As shown, the PVAG10 cross-section is relatively smooth with fewer undulations, indicating that glycerol has a strong plasticizing effect on PVA segments, making the material more prone to flexible deformation upon fracture. In contrast, the PVAP10 cross-section is rougher, with more undulations and tear marks, indicating that the movement of PVA segments in the glycerol phosphate system is more restricted, resulting in higher rigidity and more pronounced brittle fracture characteristics. This is consistent with the FTIR and XRD results: glycerol phosphate can form strong hydrogen bonds with PVA and promote the formation of locally ordered structures in the PVA phase. Therefore, the increased strength of PVAP10 mainly comes from hydrogen bond reconstruction, segment association, and local ordering, rather than simple plasticization; at the same time, this structural constraint also increases the difficulty for water molecules to penetrate and disrupt the segment network.
[0138] like Figure 9As shown, uniformly distributed salt precipitation structures were observed in PVAP10-1, PVAP10-2, and PVAP10-4, and the precipitated phases were tightly bonded to the PVA matrix. This indicates that the two types of water-soluble salts can be well dispersed during thermoplastic processing and drying film formation, forming microcrystals, localized enrichment regions, or co-precipitation nodes. This result corroborates the conclusion in XRD that "PVA phase crystallinity decreases but salt microcrystals / fine precipitation structures appear," indicating that the salt components, on the one hand, interfere with the orderly stacking of PVA segments, and on the other hand, form salt microcrystals in the matrix. High-magnification SEM further revealed the structural differences between SLS-Na and GAS. The SLS-Na precipitated structures are relatively large, possibly due to strong intermolecular π-π interactions, which tend to form larger local precipitates or micro-aggregates, making it difficult for them to fully penetrate the PVA segments. In contrast, the GAS precipitated structures are smaller and more compact, indicating that they more easily penetrate the amorphous regions or intersegmental spaces of PVA. Some GAS may exist in the amorphous phase of PVA as finely dispersed phases, ion-associated phases, or plasticized phases. More complex multi-scale precipitated structures can be observed in the compound system, suggesting that SLS-Na and GAS interfere with each other and synergistically precipitate during film formation, rather than being simply dispersed independently.
[0139] This microstructure explains the multifunctional synergy of the composite film. In the dry state, uniformly distributed salt crystallites or co-precipitated nodes act as physical reinforcement points, working with hydrogen bonds and interfacial interactions between PVA segments to restrict segment slip and improve load transfer efficiency. Upon contact with water, SLS-Na and GAS preferentially dissolve due to their good hydrophilicity and water solubility, leaving pores and interfacial defects inside the film, promoting water molecule entry into the amorphous region of PVA and weakening the hydrogen bond network. Therefore, the same type of salt precipitation structure acts as reinforcement nodes in the dry state, but transforms into sacrificial mass transfer channels in an aqueous environment. Different salt precipitation morphologies also determine performance differences. The larger precipitates formed by SLS-Na are more likely to create interconnected pores after dissolution, which is conducive to water entry; the fine and dense structure formed by GAS is more likely to weaken PVA phase crystallization, but its local ion concentration changes after dissolution may affect complete dissolution in the later stage. Therefore, water solubility is not only determined by the crystallinity of PVA, but also by the size of the salt precipitation, dispersion uniformity, pore connectivity, and ionic environment. Flame retardant properties mainly depend on the good dispersion of glyceryl phosphate, SLS-Na, and GAS in the PVA matrix, enabling phosphorus-containing structures, lignin-based char-forming structures, and nitrogen-containing salt components to synergistically participate in char layer construction and combustion inhibition during heating. Therefore, morphological uniformity not only affects the transfer of mechanical loads and moisture diffusion, but also determines the spatial matching of acid sources, gas sources, and char sources at the combustion interface, thus causing the same microstructure to exhibit different functions under dry, wet, and heated conditions.
[0140] In summary, the multi-component synergistic effect employed in this invention endows the membrane material with excellent dry mechanical properties. Glyceryl phosphate not only plays a plasticizing role but also effectively strengthens the hydrogen bond network between PVA chains. Although the introduction of the two salts reduces the matrix crystallinity to 18.4% due to macromolecular steric hindrance, the microcrystalline nodes precipitated from the salt phase and the hydrogen bond network form a synergistic stress transfer, significantly increasing the tensile strength of the optimally formulated sample from 36.3 MPa to 130.1 MPa. Simultaneously, this system constructs a highly efficient intumescent flame-retardant network. SLS-Na, GAS, and glyceryl phosphate, upon heating, respectively function as a char source, gas source, and acid source, producing a synergistic effect and generating a dense, heat-insulating char layer in situ. This increases the limiting oxygen index of the sample to 28.9% and achieves the UL94 V-0 level. More importantly, the composite membrane material successfully overcomes the mass transfer lag problem caused by the dense fire-resistant network by utilizing the preferential dissolution of water-soluble dual salts upon contact with water. After the salts dissolve, interconnected micropores are generated in situ within the matrix, and the reconstruction of the water molecule diffusion path significantly accelerates the deentanglement of polymer chains, reducing the complete dissolution time to 7.1 min. This invention proposes and verifies a design concept that synergistically balances multiple properties of polymer films by regulating the hydrogen bond network and salt phase pore formation, providing a solid theoretical foundation for developing novel green packaging materials that meet the requirements of continuous processing, dense storage safety, and rapid ecological disposal.
[0141] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.
Claims
1. A method for preparing a water-soluble dual-salt flame-retardant polyvinyl alcohol composite film based on glycerol phosphate plasticizing modification, characterized in that... Includes the following steps: (1) By mass parts, the following raw material components are mixed and then subjected to swelling and plasticizing modification to obtain pre-plasticized PVA: 50-70 servings of PVA 5-15 parts of glyceryl phosphate 20-35 parts deionized water 5-15 parts of water-soluble flame retardant; The water-soluble flame retardant is sodium lignosulfonate and guanidine aminosulfonate; (2) The preplasticized PVA obtained in step (1) is melt-extruded and granulated to prepare PVA composite granules; (3) The PVA composite granules obtained in step (2) are hot-pressed into a film and then dried to prepare a water-soluble double salt flame retardant polyvinyl alcohol composite film.
2. The method according to claim 1, characterized in that: The PVA mentioned in step (1) has a degree of polymerization of 1500~2400 and a degree of hydrolysis of 88~92%.
3. The method according to claim 1, characterized in that: The swelling and plasticizing modification described in step (1) involves first mixing glyceryl phosphate, deionized water and water-soluble flame retardant evenly to prepare a plasticizing flame retardant solution, then fully mixing the plasticizing flame retardant solution with PVA to uniformly coat the PVA surface, and then sealing and heat-preserving it at a temperature of 50~70 ℃ for 24~72h.
4. The method according to claim 1, characterized in that: In step (1), the mass ratio of sodium lignosulfonate to guanidine aminosulfonate is (1~4):(1~4).
5. The method according to claim 1, characterized in that: Step (2) in the melt extrusion granulation process also includes the addition of additives.
6. The method according to claim 1, characterized in that: In step (2), the preplasticized PVA is melt-extruded and granulated using a screw extruder with the temperature of each zone set to 80~135 ℃ and the screw speed to 15~35 rpm.
7. The method according to claim 1, characterized in that: The PVA composite granules described in step (3) are hot-pressed into a film. Specifically, the PVA composite granules are laid flat in a hot-pressing mold and hot-pressed into a film at 160~190 ℃ and 5~10 MPa, and then cooled to 23~27 ℃ under pressure.
8. The method according to claim 1, characterized in that: The drying process described in step (3) is a drying process at a temperature of 40~90 ℃ for 12~48 h.
Citation Information
Patent Citations
Method for preparing high-performance PVA / PBAT (polyvinyl acetate / poly (butylene adipate-co-terephthalate)) composite film by blow molding
CN120040810A
Plasticizer formula for hot melting process of partially alcoholized polyvinyl alcohol and process
CN103113698A
Tannic acid-based single-component intumescent flame retardant as well as preparation method and application thereof
CN115678102A